Multispecies analysis of the role of epigenetic factors in aging - Müller, Miriam (Jihočeská univerzita, 2022)
The following thesis provides the results of a multispecies analysis that was done to identify expression patterns of 209 genes encoding epigenetic factors that are associated with aging and longevity. The first part of the analysis investigated changes in the gene expression with aging for the long-lived species human and naked mole rat and the short-lived species mouse and rat. The second part aimed to further analyse the baseline expression levels of these genes in the long-lived species bowhead whale, human, blind mole rat and naked mole rat when compared to the short-lived species rat, mouse, marmoset and guinea pig. To achieve this, a number of Python scripts were developed, investigating the expression of epigenetic factors that potentially contribute to longevity.
Multispecies analysis of the role of epigenetic factors in aging